Silicon Effects on Biomass Carbon and Phytolith-Occluded Carbon in Grasslands Under High-Salinity Conditions - Liu, Linan; Song, Zhaoliang; Yu, Changxun; Yu, Guanghui; Ellam, Rob M.; Liu, Hongyan; Singh, Bhupinder Pal; Wang, Hailong (Frontiers in Plant Science, 2020)
Changes in climate and land use are causing grasslands to suffer increasingly from abiotic stresses, including soil salinization. Silicon (Si) amendment has been frequently proposed to improve plant resistance to multiple biotic and abiotic stresses and increase ecosystem productivity while controlling the biogeochemical carbon (C) cycle. However, the effects of Si on plant C distribution and accumulation in salt-suffering grasslands are still unclear. In this study, we investigated how salt ions affected major elemental composition in plants and whether Si enhanced biomass C accumulation in grassland species in situ. In samples from the margins of salt lakes, our results showed that the differing distance away from the shore resulted in distinctive phytocoenosis, including halophyte species and moderately salt-tolerant grasses, which are closely related to changing soil properties. Different salinity (Na+/K+, ranging from 0.02 to 11.8) in plants caused negative effects on plant C content that decreased from 53.9% to 29.2% with the increase in salinity. Plant Si storage (0.02–2.29 g Si m-2 dry weight (dw)) and plant Si content (0.53% to 2.58%) were positively correlated with bioavailable Si in soils (ranging from 94.4 to 192 mg kg-1). Although C contents in plants and phytoliths were negatively correlated with plant Si content, biomass C accumulation (1.90–83.5 g C m-2 dw) increased due to the increase of Si storage in plants. Plant phytolith-occluded carbon (PhytOC) increased from 0.07 to 0.28‰ of dry mass with the increase of Si content in moderately salt-tolerant grasses. This study demonstrates the potential of Si in mediating plant salinity and C assimilation, providing a reference for potential manipulation of long-term C sequestration via PhytOC production and biomass C accumulation in Si-accumulator dominated grasslands.